Wutanfall: emotional entanglements in the East German punk subculture. Issue 4 (2nd October 2022) - Hayton, Jeff
ABSTRACT: Emotions played a critical role in the history of East German punk subculture. Emerging in the late 1970s, punks challenged the SED state and subverted socialist norms through their music, fashion, and lifestyle. However, punk emotional praxis was marked not by opposition to state socialism, as earlier authors have suggested, but rather by deep entanglements. By exploring the punk subculture in the early 1980s, the author argues that youths engaged in a wide variety of practices that undermined the SED regime, even if they could not be divorced from the East German context. As such, punk emotions were predicated on complex emotional engagement requiring interaction, negotiation, and response by state authorities – and vice versa. This emotional entanglement, in turn, helped structure the subculture and give youth enactments their meaning. Thus, the research presented here revises binary interpretations of East German punk emotionology and sheds light on the functioning of both the subculture and state socialism in the last decade of the GDR.